2019
DOI: 10.1177/0040517519870317
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of denim fabric wastes into high-performance composites using the needle-punching nonwoven fabrication route

Abstract: At present, a large number of waste textiles are disposed through incineration and burial, which cause serious environmental pollution. Therefore, recycling textile wastes into high mechanical products with eco-friendly method is an urgent issue. Based on the above status quo, three kinds of 3D waste denim fiber needled felts/epoxy composites (3DWECs) with different areal densities of the mono-layer fiber web were designed and fabricated, and the effect of the areal density of the mono-layer fiber web on its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…They showed that the developed composites are potential materials for furniture materials. Xue Meng et al [ 25 ] developed epoxy composites reinforced with nonwovens produced using fibers extracted from waste denim for construction and building materials. Sadikoglu et al [ 26 ] developed composites reinforced with polyester textile waste and urea‐formaldehyde as a matrix for replacing fiberboard and medium‐density fiberboard.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the developed composites are potential materials for furniture materials. Xue Meng et al [ 25 ] developed epoxy composites reinforced with nonwovens produced using fibers extracted from waste denim for construction and building materials. Sadikoglu et al [ 26 ] developed composites reinforced with polyester textile waste and urea‐formaldehyde as a matrix for replacing fiberboard and medium‐density fiberboard.…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental analysis, it has been verified that the tensile, bending, and compressive resistance was higher in the case of intermediate areal density among the three choices. Yet, given the effective ability of the fibers, regardless of the type, in the load bearing for all cases, the realized composites have been considered satisfactory for the replacement in some particle boards [ 57 ].…”
Section: Recent Applications Of Waste Textiles Into Organic or Inomentioning
confidence: 99%
“…Figure 1 shows the main production process of the 3DNWCFCs. Waste jeans were transformed into waste cotton fibers (length: 10–25 mm 9 ; diameter: 15–25 µm 29 ) by the cloth opener apparatus (HY2-15). Afterwards, the waste cotton fibers were combed into original fiber webs, which would be laid layer upon layer by the web-forming machine (WL-GP-B-800) to form fiber webs with certain thickness, strength and uniformity according to the FVCs.…”
Section: Materials and Testsmentioning
confidence: 99%
“…58 Waste textiles and fibers with wide application prospects can be used in the field of composite materials to replace some part of the composite products. 911 Our previous studies have shown that the waste cotton fiber reinforced composites have good mechanical properties. 9 The mechanical properties of the waste cotton fiber reinforced composites we made are better than that of the best particle board on the market.…”
mentioning
confidence: 99%
See 1 more Smart Citation